2021
DOI: 10.3390/cells10020431
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the HBP Function Increases Pancreatic Cancer Cell Sensitivity to a Pan-RAS Inhibitor

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer-related death and the search for a resolutive therapy is still a challenge. Since KRAS is commonly mutated in PDAC and is one of the main drivers of PDAC progression, its inhibition should be a key strategy for treatment, especially considering the recent development of specific KRAS inhibitors. Nevertheless, the effects of KRAS inhibition can be increased through the co-inhibition of other nodes important for cancer development. One of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Recent studies reported that FR054, a specific inhibitor of PGM3, has an anti-cancer effect in breast and pancreatic cancer models, both in vitro and in vivo without having severe adverse effects [ 26 , 27 , 28 ]. Before examining the anti-cancer effect of FR054 in NSCLC, we aimed to confirm whether FR054 effectively inhibits PGM3 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that FR054, a specific inhibitor of PGM3, has an anti-cancer effect in breast and pancreatic cancer models, both in vitro and in vivo without having severe adverse effects [ 26 , 27 , 28 ]. Before examining the anti-cancer effect of FR054 in NSCLC, we aimed to confirm whether FR054 effectively inhibits PGM3 activity.…”
Section: Resultsmentioning
confidence: 99%
“…12 Similarly, suppression of the PGM3 function by a specific inhibitor FR054 improves the susceptibility of pancreatic cancer cells to a pan-RAS inhibitor. 14 PGM3 inhibition through FR054 induces breast cancer growth arrest and apoptosis. 15 Meanwhile, PGM3 expression is elevated in prostate cancer samples, suggesting a pro-oncogenic role for PGM3.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the pro-tumorigenic functions of PGM3 have been reported in cancers of breast, uterine, prostate, and pancreas. 1215 PGM3 was significantly upregulated in CRC according to The Cancer Genome Atlas (TCGA) database. However, the biological function of PGM3 in colon cancer is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Early preclinical studies confirmed its activity in blocking the KRAS pathway in NSCLC cells [180]. Using FR054 to inhibit glycosylation reactions further enhances the anticancer activity of BI-2852 against PDAC cells [181], supporting that the hexosamine biosynthesis pathway is a potential target for the treatment of KRAS-mutant cancers [182].…”
Section: Pan-kras Inhibitorsmentioning
confidence: 89%